SYNTHESIS, CHARACTERIZATION AND CATALYTIC ACTIVITY OF CATALYSTS Fe-Mo-Sb - Garrido-Schaeffer, A. (2000)
lt has been prepared six multiphasic masic catalysts of the Fe-Mo-Sb system, which were characterized by X-ray difraction, Mossbauer Spectroscopy, BET and scanning electronic microscopy. All catalysts were tested in the reaction of oxidative dehydrogenation of ethanol to acetaldehyde. The catalyst Fe2(MoO4)3 + α-Sb2O4 was showed the highest yield and selectivity to acetaldehyde following by FeSbO4 of all prepared catalysts.